Hydrogen Production by Methane Pyrolysis in a Molten‐Metal Bubble Column - Zaghloul, Nada; Kodama, Satoshi; Sekiguchi, Hidetoshi (Chemical Engineering & Technology, 2021)
Hydrogen was produced by methane pyrolysis in a molten‐metal bubble column reactor. The proposed reactor improves heat transfer to the reactant gas and allows the separation of solid carbon due to the density difference between the molten metal and produced carbon. The effects of the temperature of the molten metal and metal type on the process were studied. The kinetic parameters were estimated by using a semi‐numerical model of two reactors in series developed for the system. Molten tin, as reaction medium, showed improved kinetic parameters compared to those of the conventional tubular reactor. Tin‐copper and tin‐nickel alloys were also used as molten media to study the effect of catalytically active metals. The produced carbon was analyzed to examine its morphology and purity. Methane pyrolysis in a molten‐metal bubble column reactor is an alternative, CO2‐free method for hydrogen production. A semi‐numerical model with two reactors in series was used to estimate the reaction kinetics of methane pyrolysis in a molten‐metal bubble column reactor. The effect of molten‐metal type on the reaction kinetics was studied, and the quality of the carbon product was analyzed.